Male homosexuality and homophobia in contemporary Slovakia: A qualitative inquiry into personal online narratives - Jovanović, Srđan Mladenov (Journal of Gender and Power, 2020)
Homosexuality in Slovakia is covered in a veil of secrecy. With constant attacks by the Catholic Church and populist, traditionalist politicians, it is barely visible in society and politics, unless when discursively attacked. Similarly, homosexuality in Slovakia has failed to become a topic in the contemporary academia, with the exception of a few local works. This article, aiming to fill that gap, confronts a selection of online narratives of Slovak homosexuals via Qualitative Data Analysis through the qualitative tool, QDA Miner, including narrative analysis. Additionally, having in mind the strong propaganda of the Catholic Church against homosexuality, select homophobic narratives are analyzed via the same means.